2019
DOI: 10.1002/jsfa.9757
|View full text |Cite
|
Sign up to set email alerts
|

l‐Methionine activates Nrf2‐ARE pathway to induce endogenous antioxidant activity for depressing ROS‐derived oxidative stress in growing rats

Abstract: BACKGROUND Methionine is an essential sulfur‐containing amino acid. To elucidate the influence of l‐methionine on activation of the nuclear factor erythroid 2‐related factor 2–antioxidant responsive element (Nrf2‐ARE) antioxidant pathway to stimulate the endogenous antioxidant activity for depressing reactive oxygen species (ROS)‐derived oxidative stress, male Wistar rats were orally administered l‐methionine daily for 14 days. RESULTS With the intake of l‐methionine, Nrf2 was activated by l‐methionine through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 59 publications
2
53
0
Order By: Relevance
“…To explain this phenomenon, the view that the inflammation can be prevented by dietary antioxidants should be taken into account in this study [28]. It has been demonstrated that nuclear factor erythroid 2 (NF-E2)-related factor 2 (Nrf2) can modulate the anti-inflammatory response through the inhibition of NF-κB and upregulate antioxidant responsive element (ARE)-dependent gene expressions, such as HO-1 [11,[29][30][31]. In light of this view, a satisfactory explanation could be drawn from our previous studies, in which rice protein could exert an antioxidant capacity via activation of Nrf2 and upregulation of HO-1 expression in adult rats [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To explain this phenomenon, the view that the inflammation can be prevented by dietary antioxidants should be taken into account in this study [28]. It has been demonstrated that nuclear factor erythroid 2 (NF-E2)-related factor 2 (Nrf2) can modulate the anti-inflammatory response through the inhibition of NF-κB and upregulate antioxidant responsive element (ARE)-dependent gene expressions, such as HO-1 [11,[29][30][31]. In light of this view, a satisfactory explanation could be drawn from our previous studies, in which rice protein could exert an antioxidant capacity via activation of Nrf2 and upregulation of HO-1 expression in adult rats [11].…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous studies [6][7][8]11,24,29,30], animal studies (SCXK2012-0001, 8 February 2012) were approved and performed in conformity with the Guidelines of the Committee for the Experimental Animals of Harbin Institute of Technology (Harbin, China). Briefly, growing male Wistar rats (body weight 180-200 g) and adult male Wistar rats (body weight 390-410 g) were purchased from the Vital River Laboratories (Beijing Vital River Laboratory Animal Technology Co. Ltd., Beijing, China) and individually housed in metabolic cages in a room maintained at 22 ± 2 • C under a 12-h light-dark cycle (07:00-19:00 for light).…”
Section: Animals Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a sensor for oxidative stress, Nrf2 is tightly regulated by the Kelch‐like ECH‐associated protein 1 (Keap1) . Hence, the activation of Nrf2‐Keap1 pathway is regarded as playing a key role in inducing an antioxidant response to scavenge ROS . After 2 weeks' feeding, rice protein suppressed the expressions of Keap1 in protein and genes, leading to the activation of the Nrf2‐keap1 pathway in growing and adult rats fed with rice proteins.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Hence, the activation of Nrf2-Keap1 pathway is regarded as playing a key role in inducing an antioxidant response to scavenge ROS. 28,44,47 After 2 weeks' feeding, rice protein suppressed the expressions of Keap1 in protein and genes, leading to the activation of the Nrf2-keap1 pathway in growing and adult rats fed with rice proteins. Consequently, the ARE-driven antioxidant expression of CAT, SOD and GPx could be stimulated by rice protein feeding, showing a significantly positive correlation between nuclear contents of Nrf2 and the expressions of CAT (r = 0.8424, P < 0.05), of SOD (r = 0.8255, P < 0.05), and of GPx (r = 0.7991, P < 0.05), respectively.…”
Section: Discussionmentioning
confidence: 99%